Perilaku Pengguna Media Sosial beserta Implikasinya Ditinjau dari Perspektif Psikologi Sosial Terapan - Mulawarman Mulawarman; Aldila Dyas Nurfitri (Buletin Psikologi, 2017)
Social media becomes a new tool for many areas to perform functions and works, such as political campaign media, advertising, and teaching. However, the use of social media nowadays also raises excessive effects which could be serious problems if it was not overcame as soon as possible. There are some social media usage behaviors that should be observed, such as selfie, cyber bullying, online shopping, user-personalization, and shared- culture. Through the study of social psychology, it is expected that readers have more comprehensive perspective in looking at the phenomenon of social media hegemony as part of contemporary social reality.